Mýliti se je lidské-- - Rádl, Stanislav (Chemické listy, 2015)
The compound originally known as TIC10 or ONC201 is a new anticancer drug developed by Oncoceutics, Inc. The agent's Investigational New Drug Application for phase I/II clinical studies has been recently approved by Food & Drug Administration. However, a Scripp Institute's group revealed that the compound structure given in all documents, including patents, was erroneous and applied for a patent protection for the correct structure. Chemistry backgrounds associated with this case is reviewed together with the relevant consequences regarding the intellectual property issue.
Keywords: Intellectual Property; Chemistry Techniques, Analytical; Humans; magnetická rezonanční tomografie; bosutinib; protinádorové látky; tyrosinkinasy; isomerie; lidé; Isomerism; Antineoplastic Agents; chemické techniky analytické; Protein-Tyrosine Kinases; Crystallography, X-Ray; kvantitativní vztahy mezi strukturou a aktivitou; Apoptosis; farmaceutická technologie; Drug Compounding; apoptóza; TNF-Related Apoptosis-Inducing Ligand; krystalografie rentgenová; duševní vlastnictví; Technology, Pharmaceutical; Quantitative Structure-Activity Relationship; příprava léků; Magnetic Resonance Imaging; protein TRAIL